THE OPERATORS OF THE GENERALIZED DIFFERENTIATION OF THE FUNCTIONS IN THE CALCULATION METHOD OF STATING THE VALUE OF WIND VELOCITY FIELD IN THE ATMOSPHERE, WHICH IS BASED ON THE NAVIE-STOKS VECTOR EQUATION - Igor E. Naats; Roman A. Ryskalenko (Наука. Инновации. Технологии)
The Navie - Stoks vector equation is considered and for it creation computing algorithm on the basis of operators of the generalized differentiation of the functions corresponding to empirical data of a task, with the help of that may be state the value of wind velocity field consideration terms in it, which are formed of turbulent viscosity in the frontier layer of the atmosphere.